2023
DOI: 10.1097/md.0000000000035537
|View full text |Cite
|
Sign up to set email alerts
|

Clinical manifestations and outcomes of coronavirus disease 2019 among pediatric liver transplant recipients in the delta and omicron variant pandemic: A retrospective study

Songpon Getsuwan,
Sophida Boonsathorn,
Sujittra Chaisavaneeyakorn
et al.

Abstract: To determine the clinical manifestations and outcomes of the coronavirus disease 2019 (COVID-19) in children who underwent liver transplantation (LT). A retrospective study was conducted at a transplant center in Thailand to include LT recipients aged < 18 years who had been infected with COVID-19. Out of a total of 54 children, there were 31 probable cases (57.4%) diagnosed using an antigen test kit and 23 confirmed cases (42.6%) diagnosed using polymerase chain reaction (14 children) or severe acute respi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
0
0
Order By: Relevance
“…There was one observational study that reported an extended length of stay in children who received favipiravir, but the setting of the study was retrospective and not a well-controlled design, so this conclusion is still unclear [ 19 ]. In one trial, children with chronic liver disease with COVID-19 infection were successfully treated with favipiravir and had a favorable outcome without side effects [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…There was one observational study that reported an extended length of stay in children who received favipiravir, but the setting of the study was retrospective and not a well-controlled design, so this conclusion is still unclear [ 19 ]. In one trial, children with chronic liver disease with COVID-19 infection were successfully treated with favipiravir and had a favorable outcome without side effects [ 20 ].…”
Section: Discussionmentioning
confidence: 99%